Consumer Behaviour Toward Mobile Data Service Providers Performance In Skudai, Johor Bahru - Yeoh, Kim Hui (Universiti Malaysia Sarawak (UNIMAS), 2016)
The consumer behaviour toward mobile data service performance depends on service quality, social influence, purchase intention and promotion. This study proposed a conceptual framework with modified of the Theory of Planned Behavior in order to examine the consumer behaviour toward mobile data service performance. The questionnaire are distributed by convenient sampling method. Data collected from 400 respondents at Skudai area were used to test the proposed model. The result showed that the service quality is the strong predictors of consumer behaviour based on Pearson Correlation Coefficient and Multiple Regression analysis. Managerial and Theoretical implications have been discussed to provide insight and useful information to the telecommunication industry. The limitations faced in this study will be addressed and recommendations will be developed to assist future researchers in managing these limitation.